4CPS-234 Impact of an intensive monitoring programme on methotrexate elimination. (23rd March 2022) - Sebastián, C; Castells, G; Manzaneque, A; Salazar, F; Rodrigo, M; Meca, N; Nicolás, J
Abstract : Background and importance: High-dose methotrexate (hDMTX) can cause significant toxicities, especially renal ones. Adequate patient management is essential to prevent them and reduce hospital stay. Aim and objectives: To determine if the implementation of an intensive monitoring programme (IMP) of MTX concentrations ([MTX]) and supporting measures improved the methotrexate clearance in comparison with a standard monitoring programme (SMP) in patients with haematological malignancies. Material and methods: Retrospective observational study was performed including patients admitted to a haematology ward between January 2020 and September 2021, all treated at hDMTX (≥500 mg/m 2 ). SMP consisted of (A) daily pH monitoring and (B) pharmacokinetic monitoring 48 hours after starting infusion and every 24 hours until [MTX]<0.2 µM. IMP consisted of (A) 6-hourly pH monitoring and (B) pharmacokinetic monitoring at 12, 23, 36 and 42 hours after starting infusion. Then, individualised monitoring based on a Bayesian estimation of MTX clearance and volume of distribution until [MTX]<0.2 µM. Demographic and treatment variables were collected from hospital health electronic records. Participants were divided into two groups: IMP and SMP. The principal variable was defined as time (days) to [MTX]<0.2 µM from start of infusion. Statistical analysis was conducted with STATA version 17.1. Mann–Whitney test was performed to compare medians of the principal variable. Other variables were analysed with descriptive statistics. Results: Demographic and treatment variables are summarised below: 41 treatment courses with MTX were included (19 SMP/22 IMP). Median time to [MTX]<0.2 µM in SMP group was 3 (range 2–12) days and for IMP group was 3 (range 2–4) days (p=0.2382). 4 patients in the SMP group needed 5–12 days to obtain [MTX]<0.2 µM. Conclusion and relevance: Although no statistically relevant signification was determined comparing both groups, a narrower range in the median of MTX clearance was observed in the IMP group. Thus, early MTX monitoring could possibly result in faster MTX elimination and lower length of hospital stay. References and/or acknowledgements: Conflict of interest: No conflict of interest